Experimental Investigation of Contact and Bending Stresses of Involute Gear Pair - ZAHED, MOHD HAIDAR (IRC, 2017)
Highly loaded gears experience high bending and contact stresses. Gear tooth failure will likely happen due to these stresses. The major failures that usually happen are pitting and cracked root. These failures can be overcome by knowing the bending and contact stresses of the gear. Therefore, this study is served to investigate the effects of bending and contact stresses on gears by increasing the torque to the gears. Four pairs of gears with different helix angle will be used in this study. These gears will be tested with the Gear Dynamic Stress Test Rig (GDSTR) machine which will generate torque to the gears. At the same time, Data Acquisition Software (DAQ) is used to calculate the bending and contact strain experienced at the tooth of the gears. From the strain, bending and contact stresses are calculated. The experimental values of bending and contact stresses are compared to the theoretical values which are calculated using American Gear Manufacturers Association (AGMA) equations. The results show that the theoretical and experimental values can be correlated to each other.